Evaluation of Maize Hybrids for Salt Tolerance due to Saline Irrigations through Drip in Andhra Pradesh - LATHA, M.; LAKSHMI, G. V.; HEMA, K.; VENKATRAO, P. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
A field experiment was conducted with three maize hybrids viz, Sandhya, 30V92 and DHM-117 treated with four levels of irrigations viz., BAW (Best Available Water), 2.0 dS m-1, 4.0 dSm-1, 6.0 dSm-1 through drip irrigations in Factorial Randomized Block Design with three replications. Significant yield reductions were noticed in all the three maize hybrids when irrigated with saline waters. It was found that 30V92 hybrid produced the highest yield (6008 kg ha-1) among hybrids. The soil physico-chemical properties and nutrient contents were also studied to know the impact of saline irrigation. Considerable variations were observed in soil properties also. It was found that soil pH was decreased with increase in soil EC levels. The N, P, K nutrient contents in soil were decreased with higher EC levels due to non availability of water. Highest K/Na ratio was found in 30V92 hybrid and it reveals that it is tolerant to salinity levels when compared to other hybrids.